Strategic Enhancement of Integrated Police Service Center (SPKT) Quality Based on SERVQUAL Gap Analysis to Achieve Excellent Public Service - Gatot Hadi Prasetyo; Arief Yulianto (Universitas Negeri Semarang, 2026)
This study aims to develop a strategic model to improve the quality of services at the Integrated Police Service Center (SPKT) by applying the SERVQUAL gap analysis framework. In the context of public service reform and digital transformation, SPKT plays a crucial role as the frontline of police services, directly influencing public trust and satisfaction. However, various reports and surveys indicate persistent gaps between public expectations and the actual performance of SPKT, particularly in dimensions such as responsiveness, empathy, and procedural clarity. Using a mixed-methods approach, this research combines quantitative analysis of service quality gaps across the five SERVQUAL dimensions tangibles, reliability, responsiveness, assurance, and empathy with qualitative validation through interviews and focus group discussions. The study was conducted at the Grobogan Police Department, involving community members as service users and key stakeholders as informants. Findings reveal significant negative gaps in several service dimensions, indicating areas where public expectations exceed perceived service delivery. Responsiveness and assurance emerged as the most critical dimensions requiring improvement. Furthermore, the study highlights the limited integration of digital service platforms with human-centered service quality, emphasizing the need for a balanced approach that combines technological innovation with empathetic, transparent, and reliable human interaction. The research contributes theoretically by expanding the application of SERVQUAL in the context of police services in Indonesia, an area that remains underexplored. Practically, it offers a validated strategic model tailored to the operational realities of SPKT, providing actionable recommendations for service enhancement. The model emphasizes continuous training, stakeholder engagement, and the integration of ethical values and digital tools to support sustainable public service excellence.